2004
DOI: 10.1182/blood-2004-03-1154
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of pediatric acute myelogenous leukemia

Abstract: Contemporary treatment of pediatric acute myeloid leukemia (AML) requires the assignment of patients to specific risk groups. To explore whether expression profiling of leukemic blasts could accurately distinguish between the known risk groups of AML, we analyzed 130 pediatric and 20 adult AML diagnostic bone marrow or peripheral blood samples using the Affymetrix U133A microarray. Class discriminating genes were identified for each of the major prognostic subtypes of pediatric AML, including t(15;17) [ PML-RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
418
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 399 publications
(461 citation statements)
references
References 66 publications
40
418
1
2
Order By: Relevance
“…Hence, the incidence of MLL-rearranged AML decreases with age. This is in contrast to the frequency of MLL-PTD, which is equally low in pediatric AML, ranging from 1 to 10% depending on the screening method, 13,[37][38][39] as well as in adult AML, in the range of 5-10%. 37,[40][41][42][43][44][45][46][47] The different translocation partners of the rearranged MLL gene So far, more than 60 different fusion partners of MLL have been identified.…”
Section: Epidemiology Of Mll Aberrations In Pediatric Amlmentioning
confidence: 64%
See 4 more Smart Citations
“…Hence, the incidence of MLL-rearranged AML decreases with age. This is in contrast to the frequency of MLL-PTD, which is equally low in pediatric AML, ranging from 1 to 10% depending on the screening method, 13,[37][38][39] as well as in adult AML, in the range of 5-10%. 37,[40][41][42][43][44][45][46][47] The different translocation partners of the rearranged MLL gene So far, more than 60 different fusion partners of MLL have been identified.…”
Section: Epidemiology Of Mll Aberrations In Pediatric Amlmentioning
confidence: 64%
“…61 In gene expression profiling (GEP) studies, MLL-rearranged cases clustered together as one group in AML as well as in ALL. 13,[62][63][64] However, our laboratory showed that within MLL-rearranged infant ALL each type of MLL translocation is associated with a translocation-specific gene expression signature. 65 We identified a specific gene expression signature for the total group of MLL-rearranged AML cases, 12 but were also able to identify a specific signature for t(9;11)(p22;q23).…”
Section: Epidemiology Of Mll Aberrations In Pediatric Amlmentioning
confidence: 88%
See 3 more Smart Citations